Emotional expressiveness and avoidance in narratives of unaccompanied refugee minors - Julia Huemer; Kristin Nelson; Niranjan Karnik; Sabine Völkl-Kernstock; Stefan Seidel; Nina Ebner; Erika Ryst; Max Friedrich; Richard J. Shaw; Cassey Realubit; Hans Steiner; Katrin Skala (European Journal of Psychotraumatology, 2016)
Objective: The aim of this study was to examine a cohort of unaccompanied refugee minors (URMs) by means of psycholinguistic methods in order to obtain a more subtle picture of their degree of traumatization. Methods: Twenty-eight participants were included in the Stress-Inducing Speech Task (SIST) consisting of a free association (FA) and a stress (STR) condition. Narratives were examined by means of (1) quantitative parameters (word count); (2) psycholinguistic variables (temporal junctures, TJs), narrative structure, referential activity (RA)—a measure of emotional expressivity; and (3) content analysis ratings. Results: Word count was significantly lower than in age-matched norms. In the FA condition, TJs were lower, but in the STR condition, rates were comparable. RA was significantly higher in both conditions. Content analysis ratings showed that the experiences described by these youths were potentially traumatic in nature. Conclusions: This pattern of narrative shows a mixture of fulfilling the task demand, while containing an emotionally charged narrative. Narrative structure was absent in the FA condition, but preserved in the STR condition, as URMs struggled with the description of non-normative events. This indicates that these youths have not yet emotionally dealt with and fully integrated their trauma experiences.